Examination of Effects of Shock and Weathering for the Antarctic L6 Chondrites, Yamato-74190 and Allan Hills-769, by the Rb-Sr Method - Ito, Akihiro; Nakamura, Noboru; Masuda, Akimasa (1980)
P(論文) Possible weathering effect on the Rb-Sr system has been examined for the Allan Hills-769 chondrite (L6) by leaching experiments. The results of measurement of leachability of K, Rb and Sr with 1 N-HCl in the weathered and fresh specimens of the meteorite which had no fusion crust suggest that the weathering effect in the antarctic ice was limited to the surface of the grains of meteorite regarding the Rb-Sr system. The results of the Rb-Sr isotopic measurement of the Yamato-74190 chondrite (L6) suggest that moderate impact events were responsible for the observed Rb-Sr isotopic disturbance. Because majority of Rb-Sr data of the mineral separates are grossly correlated for ∿ 4.5 b.y. isochron, the Rb-Sr system of this meteorite appears to have retained the nature of the early thermal metamorphism much better than the K-Ar system which shows youngest age of ∿0.36 b.y. (KANEOKA et al. : Mem. Natl Inst. Polar Res., Spec. Issue, 12,186,1979). departmental bulletin paper